Sintesis dan Karakterisasi Karbon Aktif dari Ampas Kelapa melalui Aktivasi Fisika-Kimia serta Potensinya untuk Pemurnian Biogas - Prawiranti, Yulizar; Mandasari, Weni (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
The increasing global demand for renewable energy and the urgent need to reduce greenhouse gas emissions highlight the importance of developing sustainable technologies for biogas upgrading. Coconut pulp, a plentiful agro-industrial residue rich in cellulose, hemicellulose, and lignin, offers a promising precursor for activated carbon production while addressing agricultural waste challenges. This study aimed to synthesize and characterize coconut pulp–based activated carbon through a combined physicochemical activation process and to evaluate its theoretical potential for CO₂ and H₂S adsorption in biogas purification. The preparation involved carbonization at 400 °C, sequential chemical activation using 3 N H₃PO₄ and 3 N KOH, followed by physical activation at 600 °C under semi-closed conditions. Proximate analysis revealed a moisture content of 4.665%, ash content of 0.637%, and a final yield of 12.38%, all within the Indonesian National Standard (SNI 06-3730-1995) limits except for volatile matter, which remained high due to the soft lignocellulosic nature of coconut pulp. BET surface analysis demonstrated a specific surface area of 345.57 m² g⁻¹, total pore volume of 0.1595 cc g⁻¹, and a dominant micropore area of 282.80 m² g⁻¹, indicating strong potential for small-molecule adsorption. The iodine number of 161.973 mg g⁻¹ confirmed micropore prevalence. FTIR spectra showed a marked decrease in –OH and C=O groups and the emergence of a new band near 900 cm⁻¹ (=C–H aromatic), evidencing the formation of stable aromatic domains. SEM–EDX images revealed a hierarchical pore network (macro–meso–micro) with uniform distribution and high carbon purity (96.65%) and minimal mineral residues. These structural and chemical features suggest enhanced interaction with acidic (H₂S) and non-polar (CO₂) gases through physisorption mechanisms. Compared with single-stage activation methods, the dual chemical–physical strategy provided superior surface area, pore connectivity, and carbon purity, representing a novel approach for biomass-derived adsorbents. Overall, coconut pulp–derived activated carbon synthesized via integrated physicochemical activation exhibits favorable physicochemical properties for efficient CO₂ and H₂S removal, supporting its application as a sustainable and low-cost adsorbent for biogas upgrading. Future work should include dynamic adsorption studies under real biogas conditions to validate the theoretical predictions and to optimize activation parameters for large-scale deployment.